2016
DOI: 10.3906/elk-1403-293
|View full text |Cite
|
Sign up to set email alerts
|

Energy optimization in wireless sensor networks using a hybrid K-means PSO clustering algorithm

Abstract: Abstract:Energy saving in wireless sensor networks (WSNs) is a critical problem for diversity of applications. Data aggregation between sensor nodes is huge unless a suitable sensor data flow management is adopted. Clustering the sensor nodes is considered an effective solution to this problem. Each cluster should have a controller denoted as a cluster head (CH) and a number of nodes located within its supervision area. Clustering demonstrated an effective result in forming the network into a linked hierarchy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 41 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…Then, Multi-hop PSO-based clustering scheme (MPSO) scheme was proposed for the efficient selection of cluster heads during the clustering process [12]. It was adopted by devising a superior fitness function that includes average distance, the energy of the member nodes in the cluster and number of cluster heads in the current iteration of the selection process.…”
Section: Bandi Rambabu a Venugopal Reddy Sengathir Janakiramanmentioning
confidence: 99%
“…Then, Multi-hop PSO-based clustering scheme (MPSO) scheme was proposed for the efficient selection of cluster heads during the clustering process [12]. It was adopted by devising a superior fitness function that includes average distance, the energy of the member nodes in the cluster and number of cluster heads in the current iteration of the selection process.…”
Section: Bandi Rambabu a Venugopal Reddy Sengathir Janakiramanmentioning
confidence: 99%
“…Utilizing the c-means clustering model by determining a random initial centroid [5], determine the distance between objects and normalize the data to improve the process of c-means clustering [6]. The c-means algorithm has been applied in some research, such as: (1) Hygiene : Clustering of the Parkinson'sdisease [ 7 ] [ 8 ] ,Obese management [9], Health care knowledge discovery [10]; (2) Clustering image : Satellite Image [11], Segmentation of white blood cells [12], Brain image segmentation [13], Content based image retrieval (CBIR) [14], Banana Image Segmentation [15], Hand gesture segmentation [16], Segmentation of fruits based on color features [17]; (3) Network science: Network partition [18], Wireless sensor networks [19]; (4) Academic science : Student careers [20], Predicting students Performance [21] ; (5) Customer satisfaction : Evaluate the cluster customers [22], Customer satisfaction in fast-food restaurant [23]; (6) Multimedia applications [24]; (7) Chemical oxygen demand [25]; (7) Approach to characterize road accident locations [26]; (8) Watershed classification [27]; (9) Wind speed [28]; (10) Tax based on cluster [29]; (11) Plagiarism detection System [30]; (12) Dictionary learning [31]; (13) Crime analysis [32]; (14) Connection oriented telecommunication data [33]; (15) Analyze Software Architecture [34]; (16) Prediction of atomic web services reliability [35] etc. It has shown that the cmean algorithm already implemented cases to solve the human problems…”
Section: Related Workmentioning
confidence: 99%
“…Implementation of k-Means Clustering Algorithm and PSO is able to partition a number of clusters that have been determined. The PSO algorithm is used as a search for the best initial centroid values for each cluster to be established [9]. The k-Means and PSO method approach can shorten computing time.…”
Section: Related Workmentioning
confidence: 99%